PARTISIPASI MASYARAKAT TERHADAP PEMILIHAN KEPALA KAMPUNG DI KAMPUNG YUWANAIN DI DISTRIK ARSO KABUPATEN KEEROM - Muhammad Muchsin (Universitas Cenderawasih, 2021)
Community participation is a form of community participation as a form of strengthening democracy. Community participation is not only carried out during regional head elections, but village head elections are also carried out as a form of support for leaders who represent themselves to become aspirational and accommodating leaders who are elected in the Yuwanain Village head election in Arso District, Keerom Regency. The methodology used is by combining qualitative research methods and quantitative research methods. Qualitative method through interviewing respondents. While the quantitative method is the author gives a questionnaire to the respondents by selecting the answer options and then quantitatively statistically. These two methods are used with the aim of making the data more valid and comprehensive. The results show that community participation in the election of the head of Yuwanain Village, Arso District, Keerom Regency has gone well, this can be proven in the highest percentage of 72%, and field observations